Primaquine therapy for malaria. - Baird, J; Hoffman, S (2004)
Primaquine is the only available drug for preventing relapse of malaria, and confusion surrounds its use. This review examines the wide range of clinical applications of primaquine described in the medical literature between 1946 and 2004. The risk of relapse of Plasmodium vivax malaria without primaquine therapy ranged from 5% to 80% or more, depending largely upon geographic location. Supervision of therapy profoundly impacts the risk of relapse, and almost all reports of malaria resistant to primaquine are associated with lack of such supervision. We nonetheless suspect that there is widespread resistance to the standard course of primaquine therapy, which is 15 mg primaquine base daily for 14 days. Clinical evidence confirms that a course of 15 mg daily for just 5 days, a regimen widely used in areas where malaria is endemic, has no discernible efficacy. This review supports a recommendation for a regimen of 0.5 mg/kg primaquine daily for 14 days, on the basis of superior efficacy and good tolerability and safety in nonpregnant persons without glucose-6-phosphate dehydrogenase deficiency.